Varietal Diversity in Mango: Importance, Challenges and Conservation Strategies - Kamble, Vittal; Sankaran, M; D C, Sunil Gowda (Indian Horticulture, 2025)
Mango, popularly known as the King of Fruits, holds significant cultural and economic importance in India. Indian farmers cultivate a wide array of mango varieties, ranging from popular ones like Alphonso and Dasheri to lesser-known types such as Langra and Himsagar. The diversity in mango cultivars is primarily influenced by factors such as climate, soil, and traditional agricultural practicesacross different regions of the country. Each variety exhibits distinct characteristics in terms of flavour, aroma, texture, and appearance, catering to diverse consumer preferences and culinary applications. Moreover, the geographical distribution of mango varieties in India reflects a rich diversity, with specific regions being renowned for the cultivation of particular cultivars.